2002
DOI: 10.1053/jhep.2002.31724
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor and bile salts are involved in transcriptional regulation of the gene encoding the human bile salt export pump

Abstract: The bile salt export pump (BSEP or ABCB11) mediates the adenosine triphosphate-dependent transport of bile salts across the canalicular membrane of the hepatocyte. Mutations in the corresponding ABCB11 gene cause progressive familial intrahepatic cholestasis type 2. The aim of this study was to investigate the regulation of human ABCB11 gene transcription by bile salts. First, a 1.7-kilobase human ABCB11 promoter region was cloned. Sequence analysis for possible regulatory elements showed a farnesoid X recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(166 citation statements)
references
References 31 publications
7
158
0
1
Order By: Relevance
“…8D). ABCB11 is a FXR target gene encoding for the bile salt export pump, which is heavily involved in bile acid homeostasis and plays an important role in biliary efflux of bile acids that can be quantitatively modeled in vitro with SC-PHH (Plass et al, 2002), (Liu et al, 1999). With CDCA treatment we observed a concentration-related induction of ABCB11 in cultures of cryo-HepaRG consistent with reports in SC-PHH (Yu et al, 2002).…”
Section: Active Uptake Transport Characterizationmentioning
confidence: 99%
“…8D). ABCB11 is a FXR target gene encoding for the bile salt export pump, which is heavily involved in bile acid homeostasis and plays an important role in biliary efflux of bile acids that can be quantitatively modeled in vitro with SC-PHH (Plass et al, 2002), (Liu et al, 1999). With CDCA treatment we observed a concentration-related induction of ABCB11 in cultures of cryo-HepaRG consistent with reports in SC-PHH (Yu et al, 2002).…”
Section: Active Uptake Transport Characterizationmentioning
confidence: 99%
“…3A). The mRNA levels of the gene encoding the canalicular bile salt transporter (Bsep), a well known FXR target gene (14,15), were significantly decreased in Fxr Ϫ/Ϫ mice (Fig. 3B).…”
Section: Steady-state Mrna Levels Of Genes Involved In Bile Saltmentioning
confidence: 99%
“…Activated FXR also controls expression of hepatic bile salt transporters, i.e. it induces expression of Bsep (14,15) and down-regulates expression of Ntcp via SHP (16). A recent study showed that mouse (but not rat) ASBT is also subjected to negative feedback regulation mediated by FXR via SHP-dependent repression of LRH-1 activation (17).…”
mentioning
confidence: 99%
“…On the other hand, the metabolism of bile acid is precisely regulated in the enterohepatic circulation, where the bile salt export pump (BSEP) and the ileum bile acid transporter (I-BABP) play critical roles. BSEP mediates the ATP-dependent transport of bile salts across the canalicular membrane of hepatocytes (Ananthanarayanan et al 2001, Plass et al 2002, whereas I-BABP, which is a cytosolic protein expressed in the ileum, binds bile acid with a high affinity to mediate its cytosolic transportation (Grober et al 1999). Short DNA sequences, referred to as FXR-responsive elements (FXREs), are present in the promoters of the SHP (Goodwin et al 2000, Lu et al 2000, BSEP (Ananthanarayanan et al 2001) and I-BABP genes (Grober et al 1999).…”
Section: Introductionmentioning
confidence: 99%